Cultivation of Medicinal and Aromatic Herbs in Agroforestry for Diversification under Submontane Conditions of Western Himalayas - Thakur, P. S.; Dutt, Vaishnu (Indian Journal of Agroforestry, 2020)
Intercropping between rows of widely cultivated poplar (Populus deltoides) with high value medicinal and aromatic plants may provide a good opportunity to diversify agroforestry and increase the farm returns. Four medicinal and aromatic herbal species namely, Ocimum sanctum, Spilanthes acmella, Tagetes minuta and Withania somnifera were grown successfully as intercrops between the rows of Populus hybrid, a commercial industrial tree species. The findings of the present study indicate that the diversification of farming system by growing medicinal and aromatic plants with trees on the farmland is a viable option. Tree canopies did not influence the growth and yield of economic parts of medicinal plants although some adverse effect of trees was obtained in plants growing nearer to the trees. The growth parameters like plant height and leaf area index; the yield attributes namely herbage yield and production efficiency were slightly reduced compared to the sole crops when grown in combination with the trees. The physiological parameters of medicinal plants were affected only in plants up to 1m distance from tree rows. Light transmission to the plants nearer to the tree lines was reduced. Photosynthetic rate was comparatively less in plants of all the four medicinal plant species growing immediately beneath tree canopies than that growing farther away from the trees. Out of the four spacings i.e., 8mx3m, 6mx4m, 5mx5m and 4mx6m; Populus planted at 8mx3m and 6mx4m proved to be the suitable tree spacings for no or little adverse effect on the growth and production behaviour of medicinal herbs.